A large Flow Signal Processing and Measurement Method based on Ultrasonic Gas Meter. (August 2020) - Zhu, Piao-xia; Li, Yue-zhong; Zhang, Yu-hua; Li, Meng
Abstract: Ultrasonic flowmeter is extensively used in petrochemical, metallurgical and other industries for its non-contact measurement, large measuring range, stable measurement results and no pressure loss. The time difference measurement method is adopted by the ultrasonic gas meter that can reduce the error caused by the variation of sound velocity with the temperature of the fluid. But there are some problems in the large flow point and small flow point in the time difference measurement method, such as low precision, low repeatability, poor stability. According to study the influence of flow velocity on ultrasonic echo signals, a method of variable threshold and variable gain based on peak detection is proposed and the prototype of gas ultrasonic flowmeter is designed in this paper. The national standard device, 100L automatic bell cover test device, is applied to verify the design scheme proposed in this paper. The experimental results indicates that the validity of variable threshold and variable gain ultrasonic signal processing method based on peak sampling is verified, in addition, the measurement accuracy and repeatability of the ultrasonic gas meter are enhanced at the point of large flow (large flow rate).